DEVELOPING SELF-MODIFYING CODE MODEL - Đurić, Goran; Mitrović, Časlav; Vorotović, Goran; Blagojević, Ivan; Vasić, Miloš (Journal of Applied Engineering Science, 2016)
This paper presents the technology of constructing and linearization of binary program utilized for program generation, analysis and transformation into a self-modifying code. An example model of the self-modifying software system and its experimental application in vehicle control have been presented in this paper. The module responsible for vehicle control comprising two subsystems has been created within the simulation software. The first subsystem has emerged through the classical software process developed by a human-programmer. The second subsystem has been created as a result of a separate piece of software substituting the part of a programmer in a software process part. The result of this approach is software creation in conjunction with natural and Artificial Intelligence in addition to experimental integration into the vehicle control system.